Effectiveness of different carbamide peroxide concentrations used for tooth bleaching: an in vitro study - MEIRELES, Sônia Saeger (Faculdade de Odontologia de Bauru da Universidade de São Paulo, 2012)
OBJECTIVES: This in vitro study evaluated the effectiveness of three carbamide peroxide concentrations used for tooth bleaching treatments. MATERIAL AND METHODS: Sixty bovine dental slabs (6x6x3 mm) were obtained, sequentially polished, submitted to artificial staining (baseline) and randomized into four groups (n=15), according to the bleaching agent concentration: distilled water (control), 10% (CP10), 16% (CP16) or 37% (CP37) carbamide peroxide. CP10 and CP16 were covered with 0.2 mL of the respective bleaching gels, which were applied on enamel surface for 4 h/day during two weeks. Samples of CP37 were covered with 0.2 mL of the bleaching gel for 20 min. The gel was light activated by two 40-s applications spaced by 10-min intervals. The gel was renewed and applied 3 times per clinical session. This cycle was repeated at 3 sessions with 5 days of interval between them. Tooth shade evaluations were done with a digital spectrophotometer at T0 (baseline), T1 (after 1-week of treatment) and T2 (1-week post-bleaching). Tooth shade means were statistically analyzed by Kruskal-Wallis and Friedman's tests and color parameters were analyzed by two-way ANOVA and Tukey's test (p<0.05). RESULTS: At T1 and T2 evaluations, tooth shade was significantly lighter than at baseline for all treatment groups, considering the color parameters ΔL*, Δa*, Δb*, ΔE* (p<0.001) or tooth shade means (p<0.001). CP37 group showed lower shade mean change than CP10 and CP16 at T1 (p<0.01), but this difference was not statistically significant at T2 (p>0.05). CONCLUSIONS: One week after the end of the treatment, all carbamide peroxide concentrations tested produced similar tooth color improvement.